ANALISIS PROFITABILITAS PT UNILEVER INDONESIA Tbk - Danna Solihin (LPPM University 17 Agustus 1945 Samarinda, 2020)
The development of food and beverage industry is expected to remain one of the leading sectors in supporting growth of manufacturing industry and national economy. The purpose of this study to analyze financial performance in terms of profitability ratios. Object of this research is PT Unilever Indonesia Tbk. The data used in the form of PT Unilever Indonesia Tbk’s financial statements for the periode 2017-2020 Quarter 1. This result shows that there was a decline in financial performance at PT Unilever Indonesia Tbk in the 2017-2019 period but shows increase trend in the 2019-2020 when viewed from the aspect of profitability ratios. The decline in performance was caused by decrease in sales value and profit value both of gross profit and net profit after tax, but in the 2019-2020 period there was an increase in financial performance in several ratios including the ratio of gross profit margin, net profit margin, return on assets, while return on equity ratio fluctuated in the 2017-2020 period. Viewed from the gross profit margin ratio, for the net profit margin ratio of 5,55% and return on asset ratio decreased by 1% for the 2017-2018 and 2018-2019 periods, but for the return on equity ratio decreased by 3% in the 2017-2018 period and 7% in 2019-2020 period. The decrease in sales value and net profit was caused by the decline in consumption growth of middle and lower class people.